Acute effects of visits to urban green environments on cardiovascular physiology in women: A field experiment - Lanki, Timo; Siponen, Taina; Ojala, Ann; Korpela, Kalevi; Pennanen, Arto; Tiittanen, Pekka; Tsunetsugu, Yuko; Kagawa, Takahide; Tyrväinen, Liisa (Elsevier, 2017)
Background: Epidemiological studies have reported positive associations between the amount of green space in the living environment and mental and cardiovascular human health. In a search for effect mechanisms, field studies have found short-term visits to green environments to be associated with psychological stress relief. Less evidence is available on the effect of visits on cardiovascular physiology. Objectives: To evaluate whether visits to urban green environments, in comparison to visits to a built-up environment, lead to beneficial short-term changes in indicators of cardiovascular health. Methods: Thirty-six adult female volunteers visited three different types of urban environments: an urban forest, an urban park, and a built-up city centre, in Helsinki, Finland. The visits consisted of 15 min of sedentary viewing, and 30 min of walking. During the visits, blood pressure and heart rate were measured, and electrocardiogram recorded for the determination of indicators of heart rate variability. In addition, levels of respirable ambient particles and environmental noise were monitored. Results: Visits to the green environments were associated with lower blood pressure (viewing period only), lower heart rate, and higher indices of heart rate variability [standard deviation of normal-to-normal intervals (SDNN), high frequency power] than visits to the city centre. In the green environments, heart rate decreased and SDNN increased during the visit. Associations between environment and indicators of cardiovascular health weakened slightly after inclusion of particulate air pollution and noise in the models. Conclusions: Visits to urban green environments are associated with beneficial short-term changes in cardiovascular risk factors. This can be explained by psychological stress relief with contribution from reduced air pollution and noise exposure during the visits. Future research should evaluate the amount of exposure to green environments needed for longer-term benefits for cardiovascular health.
Keywords: green space; particulate air pollution; blood pressure; heart rate; air pollution; noise